(untitled) (Research, Society and Development, 2022)
Permanent monitoring and evaluation of water bodies in urban and suburban areas are essential to control water quality. The objective of this research was to evaluate the microbiological quality of the water of the river Itapecuru in the course that runs through the city of Caxias-MA. To carry out the microbiological analysis of the water, the methodology of multiple tubes was used, which is indicated for the determination of microorganisms, such as total coliforms and thermotolerant coliforms. Initially, the presumptive test was performed, in which the positive tubes of this stage (tubes that showed lactose fermentation and gas production) were recorded and from them, the confirmatory test and the complementary test were followed. In the result of the presumptive test, the readings varied between 240 and >1,600 MPN/100 ml, in the confirmatory test for total coliforms and in the complementary test (Escherichia coli-EC) for thermotolerant coliforms, there was a variation between 14 and 1600 MPN/100 ml for both the tests. It is concluded that the upstream and central points of the river were classified as suitable and excellent for bathing and the downstream point as inappropriate.